After the Imperial Turn : Thinking with and through the Nation - Burton, Antoinette M., 1961- (Book collections on Project MUSE., 2003)
From a variety of historically grounded perspectives, this text assesses the fate of the nation as a subject of disciplinary inquiry. The 20 essays exemplify cultural approaches to histories of nationalism and imperialism even as they critically examine the implications of such approaches.